International Recommendations for the Management of Adults Treated With Ketogenic Diet Therapies. Issue 5 (October 2021) - Cervenka, Mackenzie C.; Wood, Susan; Bagary, Manny; Balabanov, Antoaneta; Bercovici, Eduard; Brown, Mesha-Gay; Devinsky, Orrin; Di Lorenzo, Cherubino; Doherty, Colin P.; Felton, Elizabeth; Healy, Laura A.; Klein, Pavel; et al.
Abstract : Objective: To evaluate current clinical practices and evidence-based literature to establish preliminary recommendations for the management of adults using ketogenic diet therapies (KDTs). Methods: A 12-topic survey was distributed to international experts on KDTs in adults consisting of neurologists and dietitians at medical institutions providing KDTs to adults with epilepsy and other neurologic disorders. Panel survey responses were tabulated by the authors to determine the common and disparate practices between institutions and to compare these practices in adults with KDT recommendations in children and the medical literature. Recommendations are based on a combination of clinical evidence and expert opinion regarding management of KDTs. Results: Surveys were obtained from 20 medical institutions with >2, 000 adult patients treated with KDTs for epilepsy or other neurologic disorders. Common side effects reported are similar to those observed in children, and recommendations for management are comparable with important distinctions, which are emphasized. Institutions differ with regard to recommended biochemical assessment, screening, monitoring, and concern for long-term side effects, and further investigation is warranted to determine the optimal clinical management. Differences also exist between screening and monitoring practices among adult and pediatric providers. Conclusions: KDTs may be safe and effective in treating adults with drug-resistant epilepsy, and there is emerging evidence supporting the use in other adult neurologic disorders and general medical conditions as well. Therefore, expert recommendations to guide optimal care are critical as well as further evidence-based investigation.